Electrochemical Determination of Sildenafil Using Ni/UiO-66-Modified Electrode - Le Huu Trinh; Nguyen Van Hien; Nguyen Quang Man; Dinh Quang Khieu (Journal of Nanotechnology, 2025)
The present article utilized a voltammetric sensor based on a metal-organic framework from the University of Oslo −66/nickel (Ni/UiO-66) to determine sildenafil (SIL). X-ray diffraction, scanning electron microscopy, and electrochemical techniques were employed to characterize various physicochemical properties of Ni/UiO-66. Doping Ni into UiO-66 does not alter the UiO-66 framework. The prepared Ni/UiO-66 exhibited a substantial surface area of approximately 1060.3–1200.3 m2⋅g−1. Its morphology consisted of particles measuring around 240–420 nm with well-defined octahedral geometry. Ni/UiO-66 demonstrated good electrocatalytic oxidation activity toward SIL oxidation, showing significant voltammetric responses, likely due to the combined effects of UiO-66 and NiO. The electrochemical kinetics study indicated that the electrocatalytic oxidation of SIL is irreversible and involves a one proton/one electron mechanism. The oxidation peak current of SIL is linear with respect to SIL concentration in the range of 0.25–1.99 μM, with a low detection limit of 0.50 μM. Furthermore, Ni/UiO-66 exhibited high selectivity, reproducibility, and repeatability. The proposed Ni/UiO-66/GCE was utilized to measure SIL in human urine, yielding satisfactory recoveries.